Serve analysis of elite European table tennis matches - Djokic, Z.; Malagoli Lanzoni, I.; Katsikadelis, M.; Straub, G. (International Journal of Racket Sports Science, 2020)
The purpose of this study was to analyze the serve activities of elite European table tennis players. Twenty matches (78 games, 1466 points) of semifinal and final German League and Europe TOP 16 in men`s (in the top 30 of ETTU Rank list) were analyzed. Differences in serving activities (type, stroke type, outcome and placement) were analyzed according results outcome of match, game, point, phase of the game and type of games. Results showed that forehand short serve prevailed (76.9%) instead other types of serve, mostly placed in the middle of the table on the opponent`s backhand side. Percentage of point won directly with serve was 11.6%, points won with 3rd stroke - 22.4% and points won with 5th stroke after serve (10.9%). Lost points after serve mostly were after 3rd stroke (25.0%) and after 5th stroke (22.4%) and serve errors were noted in 1.5% of all analyzed points. In the 3rd phase of the game serve points were won mostly with 3rd and 5th stroke instead previous phases of the game. Results of Pearson`s chi-squared test showed an association between match outcomes and serve type and outcome, serve type and outcome considering phase of the game and different type of games with serve type, outcome and placing zones.